PUSAT KEBUGARAN DENGAN KONSEP ARSITEKTUR BIOFILIK DI KOTA TANJUNG - Rahma, Fitria; Nurfansyah, Nurfansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The design of this fitness center is motivated by everyone's need for a balanced state of mind, body and soul. Through these needs, people are starting to realize that they need to come back and start a holistic lifestyle. The purpose of this design is to provide a place that facilitates wellness-based activities in one place by paying attention to the interaction between space and nature. By utilizing the connection between humans and nature, the wellness center is planned to use the concept of biophilic architecture because it is synonymous with good natural use patterns and the use of design methods by utilizing 5 natural elements as the design method.